Upgrading iron and removing phosphorus of high phosphorus oolitic iron ore by segregation roasting with calcium chloride and calcium hypochlorite - Xiao J.; Ding W.; Peng Y.; Wu Qi.; Chen Z.; Wang Z.; Wang J.; Peng T. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The iron-bearing ore, existing in the form of oolite, was mainly composed of hematite, limonite, daphnite, and collophane. The harmful element phosphorus content was 1.56%, belonging to high phosphorus ooliticiron ore in western Hubei. In this study, segregation roasting and low intensity magnetic separation techniques were applied for upgrading iron and removing phosphorus. The ores, the chlorinating agent, and the reducing agent were mixed into the roasting furnace for segregation roasting. After being transferred from the weak magnetic minerals to the strong ones, the iron was recovered by low intensity magnetic separation. During segregation roasting, new ore phases, metallic iron (Fe), a small amount of ferroferric oxide (Fe3O4), and ferrous oxide (FeO) could be observed. The results showed that the iron concentrate with the Fe content of 90.3%, the phosphorus content of 0.15%, and the iron recovery of 92.9% were obtained under the segregation roasting temperature of 1273 K, and the roasting time of 90 min, CaCl2 (calcium chloride) 20%, Ca (ClO)2 (calcium hypochlorite) 3%, the dosage of coke 20%, and low intensity magnetic separation field intensity 0.12 T.